Microstructural characteristics and mechanical properties of bobbin tool friction stir welded 2A14-T6 aluminum alloy. (January 2015) - Zhang, Huijie; Wang, Min; Zhang, Xiao; Yang, Guangxin
Highlights: BT-FSW of 2A14-T6 high strength aluminum alloy was conducted. Upper WNZ has smaller grains than lower WNZ due to higher heat dissipation level. Flat feature on bobbin tool pin can cause material to be insufficiently stirred. The insufficiently stirred zone largely affects fracture feature of BT-FSW joint. Abstract: 2A14-T6 aluminum alloy was bobbin tool friction stir welded (BT-FSW) at various welding speeds. The microstructural analysis indicates that in the weld nugget the grains of the upper layer are smaller than those of the lower layer, which should be attributed to the larger extent of heat dissipation through the top shoulder. An ellipse-shaped region and a triangle-shaped region characterized by large elongated grain structures are found in the middle layer of the weld nugget of BT-FSW joints. The insufficient material plastic deformation caused by the flat feature of tool pin is believed to be the reason for the formation of the both regions. The insufficiently stirred regions can significantly affect the fracture features of joints during tensile test. At low welding speeds, the joints are all fractured along the border of the ellipse-shaped region. While at high welding speeds, the fracture path is just through the triangle-shaped region. With increasing welding speed, the joint strength is firstly increased to a peak and then shows a sharp decrease due to the occurrence of void defects. A maximum strength efficiency of 75% is achieved in this study.